1989
DOI: 10.1128/mcb.9.11.4587
|View full text |Cite
|
Sign up to set email alerts
|

Response of bone marrow stromal cells to adipogenic antagonists.

Abstract: Adipocytes constitute a major part of the bone marrow stroma in vivo and may play an active role in lymphohematopoiesis. Earlier studies had shown that the bone marrow stromal cell done BMS2 was capable of adipocyte differentiation in vitro, in addition to its well-defined ability to support B lymphopoiesis. We now demonstrate that the process of adipogenesis in this functional bone marrow stromal cell clone can be inhibited by the cytokines interleukin-la, tumor necrosis factor, and transforming growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…In vitro, adipocyte differentiation by stromal cells is accompanied by a loss of gene markers consistent with an osteoblast-like phenotype, including osteocalcin, type I and type I11 collagen, and osteopontin [Beresford et al, 1992; Dorheim et al, 19931. It has been suggested that osteogenic inductive cytokines may act as negative regulators of adipogenesis [Bennett et al, 1991; Beresford et al, 19921.The current work tests this hypothesis using the BMSB cell line as a multi-potent bone marrow stromal cell model [Pietrangeli et al, 1988;Gimble et al, 1989 Dorheim et al, 19931. These cells support lympho-hematopoiesis, undergo adipocyte differentiation, and constitutively display gene markers consistent with an osteoblast phenotype.…”
mentioning
confidence: 63%
“…In vitro, adipocyte differentiation by stromal cells is accompanied by a loss of gene markers consistent with an osteoblast-like phenotype, including osteocalcin, type I and type I11 collagen, and osteopontin [Beresford et al, 1992; Dorheim et al, 19931. It has been suggested that osteogenic inductive cytokines may act as negative regulators of adipogenesis [Bennett et al, 1991; Beresford et al, 19921.The current work tests this hypothesis using the BMSB cell line as a multi-potent bone marrow stromal cell model [Pietrangeli et al, 1988;Gimble et al, 1989 Dorheim et al, 19931. These cells support lympho-hematopoiesis, undergo adipocyte differentiation, and constitutively display gene markers consistent with an osteoblast phenotype.…”
mentioning
confidence: 63%
“…Earlier studies had associated BM adipocytes with increased M@-CSF and granulocyte-M@-CSF production based on biological assays [12,68]. BMM adipocytes also retained the ability to markedly increase their steady-state level of IL 6 mRNA in response to the cytokines IL1, TGF-P and TNE Each of these cytokines (IL1, TGF-P, TNF) has been to act as an adipogenic antagonist on BMS2 cells (Gimble et al, in press) [62,[69][70][71][72][73][74]. This suggests that the differentiation state* and functional activity of stromal cells can be regulated by factors released locally in the BM microenvironment in addition to more classical endocrine hormones.…”
Section: Discussionmentioning
confidence: 97%
“…These lines have been derived either directly from adipose tissue or from fetal fibroblasts [Ailhaud, 19821. Although many bone marrow pre-adipocyte stromal cell lines have been cloned, studies examining their adipocyte differentiation at the molecular level are limited [Gimble et al, 1989[Gimble et al, , 1990Gimble, 1990;Grigoriadis et al, 1990;Watanabe and Takano, 19911. In the lymphopoietic-supporting BMS2 stromal cell line, adipogenesis correlated with the induction of aP2, adipsin, and LPL steady state mRNA levels as well as increased enzyme activity for glycerophosphate dehydrogenase (GPD) and LPL [Gimble et al, 19901.…”
Section: Discussionmentioning
confidence: 99%
“…Northern blots were prepared with 10-20 mcg of total RNA per lane according to the method of Thomas [Gimble et al, 1989;Thomas, 19801.…”
Section: Rna Purification and Northern Blot Analysismentioning
confidence: 99%